How Shigella Utilizes Ca2+ Jagged Edge Signals during Invasion of Epithelial Cells - Bonnet, Mariette; Tran Van Nhieu, Guy (Frontiers in Cellular and Infection Microbiology, 2016)
Shigella, the causative agent of bacillary dysentery invades intestinal epithelial cells using a type III secretion system (T3SS). Through the injection of type III effectors, Shigella manipulates the actin cytoskeleton to induce its internalization in epithelial cells. At early invasion stages, Shigella induces atypical Ca2+ responses confined at entry sites allowing local cytoskeletal remodeling for bacteria engulfment. Global Ca2+ increase in the cell triggers the opening of connexin hemichannels at the plasma membrane that releases ATP in the extracellular milieu, favoring Shigella invasion and spreading through purinergic receptor signaling. During intracellular replication, Shigella regulates inflammatory and death pathways to disseminate within the epithelium. At later stages of infection, Shigella downregulates hemichannel opening and the release of extracellular ATP to dampen inflammatory signals. To avoid premature cell death, Shigella activates cell survival by upregulating the PI3K/Akt pathway and downregulating the levels of p53. Furthermore, Shigella interferes with pro-apoptotic caspases, and orients infected cells towards a slow necrotic cell death linked to mitochondrial Ca2+ overload. In this review, we will focus on the role of Ca2+ responses and their regulation by Shigella during the different stages of bacterial infection.